Pengaruh Pendapatan Asli Daerah dan Dana Alokasi Umum Terhadap Pertumbuhan Ekonomi Kabupaten/Kota di Provinsi Jawa Timur Tahun 2014-2018 - Dewi Susanti; Tony Seno Aji (Universitas Negeri Surabaya, 2021)
Economic growth is essentially defined as an indicator for measuring the development of the economy from one period to the next. Economic growth is also interpreted as material for assessing the success of economic development that has been achieved and is useful as a basis for planning and implementing government policies to determine the direction of development in the future. The aim of this research is to identify and analyze the effects of the Regional Original Income (PAD) and General Allocation Funds (DAU) on economic growth in the province of East Java in the period 2014-2018. This study uses secondary data from the Central Statistics Agency (BPS) and the Directorate-General for Fiscal Balance (DJPK), East Java Province. The analysis technique used in this study is a panel data regression analysis using the Fixed Effect model by performing classical assumption tests and hypotheses tests. The results of the analysis of this study show that (1) Regional Own Income has a positive effect on Economic Growth (2) General Allocation Funds have a positive effect on Economic Growth (3) Regional Original Income and General Allocation Funds together or at the same time have a significant impact on Growth Economy in East Java Regions and Cities.